2002
DOI: 10.1002/cncr.10395
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic expression of laminin γ2 chain correlates with postoperative hepatic metastasis and poor prognosis in patients with pancreatic ductal adenocarcinoma

Abstract: BACKGROUND.The laminin ␥2 chain is involved in tumor invasion and metastasis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 26 publications
4
53
0
Order By: Relevance
“…The present study demonstrated that MMP-7, cytoplasmic laminin c2 and EGFR at the invasive front of GC play a pivotal role in tumor progression and regional lymph node metastasis, whereas all these molecules except cytoplasmic laminin c2 at the control regions were not associated with any clinicopathologic parameters. In particular, cytoplasmic expression of laminin c2 in GCs might be a potent predictive factor for tumor aggressiveness as previously reported in pancreatic ductal adenocarcinomas [52]. Laminin 5 reportedly plays an important role in EMT through down-regulation of E-cadherin and translocation of b-catenin into the nuclei [53].…”
Section: (21 %) 580supporting
confidence: 55%
“…The present study demonstrated that MMP-7, cytoplasmic laminin c2 and EGFR at the invasive front of GC play a pivotal role in tumor progression and regional lymph node metastasis, whereas all these molecules except cytoplasmic laminin c2 at the control regions were not associated with any clinicopathologic parameters. In particular, cytoplasmic expression of laminin c2 in GCs might be a potent predictive factor for tumor aggressiveness as previously reported in pancreatic ductal adenocarcinomas [52]. Laminin 5 reportedly plays an important role in EMT through down-regulation of E-cadherin and translocation of b-catenin into the nuclei [53].…”
Section: (21 %) 580supporting
confidence: 55%
“…In concordance with the CGH findings, cDNA microarray analysis demonstrated that a higher proportion of these genes were dysregulated in TCV. 48,49), and TNC (cervical carcinoma, glioma, and non-small cell lung cancer; Refs. 50 -52).…”
Section: Discussionmentioning
confidence: 99%
“…8 Besides, LAMC2 monomer expression has been frequently found in the invasive front of epithelial tumors such as ADCs of the stomach, colon, pancreas, and lung, SCCs of the esophagus, head and neck, skin and lung, and transitional cell carcinoma of the bladder. 5,[9][10][11][12][13][14] Epithelialmesenchymal transition (EMT) has a critical role in the early stages of dissemination of malignant epithelial tumors leading to metastatic spread. 15 There is growing evidence that LAMC2 expression increases in the carcinoma cells undergoing EMT, [16][17][18] and that level of LAMC2 expression is regulated directly by the EMT master regulator ZEB1 and activated β-catenin in invasive colorectal carcinoma cells.…”
mentioning
confidence: 99%